Divergent male and female mate preferences do not explain incipient speciation between lizard lineages. Issue 5 (12th March 2020) - McLean, Claire A; Bartle, Richard A; Dong, Caroline M; Rankin, Katrina J; Stuart-Fox, Devi
Abstract: Diversification in sexual signals is often taken as evidence for the importance of sexual selection in speciation. However, in order for sexual selection to generate reproductive isolation between populations, both signals and mate preferences must diverge together. Furthermore, assortative mating may result from multiple behavioral mechanisms, including female mate preferences, male mate preferences, and male–male competition; yet their relative contributions are rarely evaluated. Here, we explored the role of mate preferences and male competitive ability as potential barriers to gene flow between 2 divergent lineages of the tawny dragon lizard, Ctenophorus decresii, which differ in male throat coloration. We found stronger behavioral barriers to pairings between southern lineage males and northern lineage females than between northern males and southern females, indicating incomplete and asymmetric behavioral isolating barriers. These results were driven by both male and female mate preferences rather than lineage differences in male competitive ability. Intrasexual selection is therefore unlikely to drive the outcome of secondary contact in C. decresii, despite its widely acknowledged importance in lizards. Our results are consistent with the emerging view that although both male and female mate preferences can diverge alongside sexual signals, speciation is rarely driven by divergent sexual selection alone.